Report on trainings of CLEANED (Environmental Assessment Tool for Livestock Systems) in Colombia (presential and online) - Cardoso, Juan Andres; Gonzalez Quintero, Ricardo (2024)
Livestock systems are essential for meeting the demand for animal-source foods, particularly in low- and middle-income countries, but they also present significant sustainability challenges. These systems contribute substantially to greenhouse gas emissions and place heavy demands on land and water resources. To address these issues, tools are needed to evaluate and mitigate environmental impacts while supporting sustainable livestock production. The I-CLEANED framework, which stands for Comprehensive Livestock Environmental Assessment for Improved Nutrition, Environment, and Development builds upon the CLEANED tool. This advanced version introduces a social dimension, integrating socio-economic factors such as gender, household roles, and resource access into environmental assessments. Designed for ex-ante analysis, I-CLEANED enables users to model and compare the potential environmental impacts of different livestock management scenarios before they are implemented. It is designed to assess greenhouse gas emissions, water use, soil health, and land requirements in livestock systems while accounting for diverse farming practices and social dynamics